Cardiomyocyte crosstalk with endothelium modulates cardiac structure, function, and ischemia-reperfusion injury susceptibility through erythropoietin - Marrow, Jade P.; Alshamali, Razan; Edgett, Brittany A.; Allwood, Melissa A.; Cochrane, Kyla L. S.; Al-Sabbag, Sara; Ayoub, Anmar; Ask, Kjetil; Hare, Gregory M. T.; Brunt, Keith R.; Simpson, Jeremy A. (Frontiers in Physiology, 2024)
Erythropoietin (EPO) exerts non-canonical roles beyond erythropoiesis that are developmentally, structurally, and physiologically relevant for the heart as a paracrine factor. The role for paracrine EPO signalling and cellular crosstalk in the adult is uncertain. Here, we provided novel evidence showing cardiomyocyte restricted loss of function in Epo in adult mice induced hyper-compensatory increases in Epo expression by adjacent cardiac endothelial cells via HIF-2α independent mechanisms. These hearts showed concentric cellular hypertrophy, elevated contractility and relaxation, and greater resistance to ischemia-reperfusion injury. Voluntary exercise capacity compared to control hearts was improved independent of any changes to whole-body metabolism or blood O2 content or delivery (i.e., hematocrit). Our findings suggest cardiac EPO had a localized effect within the normoxic heart, which was regulated by cell-specific EPO-reciprocity between cardiomyocytes and endothelium. Within the heart, hyper-compensated endothelial Epo expression was accompanied by elevated Vegfr1 and Vegfb RNA, that upon pharmacological pan-inhibition of VEGF-VEGFR signaling, resulted in a paradoxical upregulation in whole-heart Epo. Thus, we provide the first evidence that a novel EPO-EPOR/VEGF-VEGFR axis exists to carefully mediate cardiac homeostasis via cardiomyocyte-endothelial EPO crosstalk.